Effect of Double-Ovsynch and Presynch-Ovsynch on postpartum ovarian cysts and inactive ovary in high-yielding dairy cows - Li, Ziyuan; Luan, Shuyi; Yan, LongGang; Xie, Chengyun; Lian, Zhengjie; Yang, Mingmao; Mei, Minmin; Lin, Pengfei; Wang, Aihua; Jin, Yaping (Frontiers in Veterinary Science, 2024)
Introduction Optimizing the management of dairy cattle reproduction can reduce postpartum ovarian disease in high-yielding dairy cows and thus enhance ranch economic benefit. The hypothesis of this study was that the Double-Ovsynch (DO) protocol in high-producing dairy cows would result in a lower incidence of follicular cysts but a higher incidence of luteal cysts compared to those undergoing the Presynch-Ovsynch (PS) protocol. Methods In this experiment, 384 cows (204 primiparous and 180 multiparous) were allocated to the DO group, which followed the protocol: GnRH-7d-PGF2α-3d-GnRH-7d-Ovsynch-56 h (GnRH-7d-PGF2α-56 h-GnRH-16hTAI), starting on 39 ± 3 days in milk (DIM). Additionally, 359 cows (176 primiparous and 183 multiparous) were assigned to the PS group, which followed the protocol: PGF2α-14d-PGF2α-12d-Ovsynch-56 h, starting on 31 ± 3 DIM. In DO, B-mode ultrasound examinations were conducted 1 day after the GnRH-7d-PGF2α-3d-GnRH protocol to diagnose the presence of ovarian diseases followed by reexamination after 7 days of suspected cases. In PS, B-mode ultrasound examinations were conducted 1 day after the PGF2α-14d-PGF2α protocol to diagnose the presence of ovarian diseases followed by reexamination after 7 days. For all cows confirmed to having ovarian diseases, a second B-mode ultrasound examination was conducted at the time of the second GnRH and timed artificial insemination (TAI). If the ovary showed a normal developing follicle in combination with normal ovulation, the ovarian disease was considered to be cured. Results The current study revealed no significant difference in the overall incidence and cure rate of postpartum ovarian diseases between DO and PS (incidence rate: 3.9% vs. 6.7%, cure rate: 50% vs. 41.7%, DO vs. PS). Also, there was no significant difference in the incidence and cure rate of luteal cysts between DO and PS (incidence rate: 2.9% vs. 2.2%, cure rate: 50.0% vs. 50.0%). The incidence of follicular cysts was significantly lower in the DO group than in the PS group (0.8% vs. 2.8%, DO vs. PS, p = 0.037), but there was no significant difference in the cure rates (66.7% vs. 50%). The occurrence of inactive ovary was lower in DO compared to PS (0.2% vs. 1.7%, p = 0.047). There was no significant difference in the pregnancy rate between the DO and PS groups (48.2% vs. 41.8%), although the DO group had a higher rate. What is different from our assumption is that PS did not effectively reduce the incidence of postpartum luteal cysts.